Amelia Bedelia sets sail - Parish, Herman; Avril, Lynne, 1951- (New York, NY : Greenwillow Books, an imprint of HarperCollinsPublishers, 2015)
"Amelia Bedelia and her mother share a summer vacation home at the shore with her aunt Mary and her cousin Jason, who has a wicked sense of adventure and a nose for trouble"--
Keywords: Beaches -- Fiction; Families -- Fiction; Friendship -- Fiction; Humorous stories